Peningkatan Pengetahuan Ibu Mengenai Manajemen Laktasi dan KB Melalui Kelas Prenatal di Puskesmas Kenten Palembang - Sri Emilda; Reni Saswita (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Prenatal class is a group learning facility about health for pregnant women in a face-to-face format that aims to increase the knowledge and skills of pregnant women regarding pregnancy, childbirth, postpartum, newborn care and includes lactation management and post-delivery family planning. This community service aims to increase pregnant women's knowledge about lactation management and postpartum family planning. Participants in this activity were pregnant women at the Palembang Kenten Health Center. The target is 20 pregnant women. The method is carried out in three stages including preparation, education and evaluation. After the prenatal class, there was a significant increase in knowledge from 12.5% who had good knowledge to 100% with an average difference in pretest and posttest scores of 17.19. It is expected that midwives conduct routine prenatal classes in order to increase coverage of exclusive breastfeeding and family planning.